Configuration-Based Promotion: A New Approach to Destination Image Sustainability - Yanan Li (MDPI AG, 2021)
The assessment of tourist destination images should not only be the arrangement of multiple influencing factors. This study explores the complex causal relationship for tourist destination images based on a configuration perspective to enhance the overall tourism image using the fuzzy-set qualitative comparative analysis method. The configurational paths for promoting tourism image can be categorized into two types and nine configurations in Shandong Province. Therefore, this study recommends augmenting the tourism image of the entire region with the logical thinking of “segmentation–integration” and “enhancing strengths–supplementing weakness” and finally realizing a sustainable tourist destination image.